To the problem of keeping and using a collection of local newspapers in Scientific Library of Tuvan Institute for Humanities - Ochur, Nadezhda M. (The New Research of Tuva, 2011)
Article present a content of the newspaper collection of Scientific Library of the Tuvan Institute for Humanities and lists main problems of keeping the collection.
Keywords: Tuvan Institute for Humanities; Tuvan Scientific Research Institute of the Language; Literature and History; library; collection; newspapers; media; press; keeping